Research And Development Of The Hierarchical Switching Charging Discharging System For Continuous Sustainability - Sarban Singh, Ranjit Singh; Baljit, S.S.S.; Wong, Yan Chiew (Medwell Journals, 2018)
Integration of photovoltaic system with battery energy storage system is always seen as a better way to utilize the available energy from renewable energies. Considering continuous sustainable battery charging discharging using the solar photovoltaic, this study proposes hierarchical switching charging discharging system for solar photovoltaic system application. This study will briefly describe the methodological design of the overall system which is proposed to control between the dual and more battery energy storages. The results of the developed hardware will validate the methodological design proposed earlier and the results also, effectively justify the developed system’s performances.